1986
DOI: 10.1159/000457262
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age, Gender, and Sexual Maturation on the Caffeine Breath Test

Abstract: This study demonstrated the feasibility of utilizing the (3-13C-methyl) caffeine breath test (CBT) in children and adolescents, and examined the effect of gender, age, and puberty on the CBT. The CBT, expressed as the 2-hour accumulative exhalation of labeled CO(2) (2-hour CO(2)), was compared to the CBT results in the adult. The 2-hour CO(2) values were higher in the children than the adult, and the decrease in the CO(2) values occurred in males during late puberty and in females during early puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
6

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 22 publications
(52 reference statements)
7
45
0
6
Order By: Relevance
“…Our results could therefore indicate that adolescence could be characterized by pharmacokinetic specificities compared to the pharmacokinetics in both younger children and adults, so that the current pharmacokinetic assumption that places adults and adolescents in the same category should be reconsidered, at least for metabolized drugs. This was previously suggested for CYP 1A2, as the rate of demethylation of caffeine decreased in early puberty for girls and late puberty for boys (20). However, it must be noticed that similar sex-related differences in the pharmacokinetics of indinavir (10) and saquinavir (25), two other PIs metabolized by CYP 3A4, have been reported in adults.…”
Section: Fig 3 Goodness Of Fit Visualized On the Weighted Residualssupporting
confidence: 55%
“…Our results could therefore indicate that adolescence could be characterized by pharmacokinetic specificities compared to the pharmacokinetics in both younger children and adults, so that the current pharmacokinetic assumption that places adults and adolescents in the same category should be reconsidered, at least for metabolized drugs. This was previously suggested for CYP 1A2, as the rate of demethylation of caffeine decreased in early puberty for girls and late puberty for boys (20). However, it must be noticed that similar sex-related differences in the pharmacokinetics of indinavir (10) and saquinavir (25), two other PIs metabolized by CYP 3A4, have been reported in adults.…”
Section: Fig 3 Goodness Of Fit Visualized On the Weighted Residualssupporting
confidence: 55%
“…Multivariate analysis confirmed that the only independent predictors of the CBT were smoking status and disease state. This is in accord with previous studies showing that caffeine metabolism does not appear to be influenced by age beyond adolescence 29,30 and sex. 30,31 It generally has been accepted that the 2-hour cumulative exhalation of labeled CO 2 represents the best parameter of caffeine clearance in the adult.…”
Section: Discussionsupporting
confidence: 93%
“…The CBT values for the 51 PBB-exposed Michigan subjects (with and without detectable PBB serum levels) and our previously reported adult urban control groups of 28 healthy Illinois nonsmokers and 16 smokers (20,24), all of whom had not been exposed to PBBs, are shown in Figure 2. The PBB-exposed subjects had higher CBT values as compared to the urban nonsmokers (p = 0.02), but had CBT values not different from the urban smokers.…”
Section: Caffeine Breath ¶Istmentioning
confidence: 86%
“…The CBT and CMR may be valuable tools in biochemical epidemiology since both are safe, noninvasive, and can be readily performed in the field in subjects of all ages (24). A good correlation (r2 = 0.54, p = 0.001) was observed between the CBT and CMR, and each test has its unique advantage and disadvantages (28).…”
Section: Discussionmentioning
confidence: 99%